The Impact of Inflation Accounting on Key Audit Matters: A Study on the Technology and Information Sector of Borsa Istanbul (Third Sector Social Economic Review, 2026)
The aim of this research is to analyze the impact of IAS 29 – Financial Reporting in High-Inflation Economies, which was reinstated in Turkey in 2023, on Key Audit Matters (KAMs) in independent audit reports. The research examined the independent audit reports of 39 companies operating in the technology and information sector on Borsa Istanbul (BIST) for the 2022 and 2023 fiscal years. The document review method was used for data collection, and the obtained data were evaluated using systematic content analysis. Due to the non-normal distribution of the data, the non-parametric Wilcoxon Signed-Rank Test was used to determine the differences between periods. The findings reveal that the application of IAS 29 in 2023 emerged as a significant key audit matter in independent audit reports, with a statistically significant increase in the number of KAMs compared to 2022. Furthermore, the calculated effect size indicates that this change has a moderate impact. The results show that inflation accounting increases the complexity of the audit process, broadens the scope of auditors' professional judgment, and significantly affects the content of audit reports. In this respect, the study contributes to the literature by demonstrating the impact of inflation accounting on independent audit reporting with empirical findings.
Keywords: Audit Report; Key Audit Matters; Inflation Accounting; Independent Audit; IAS 29